PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMA SWASTA DI KOTA MANADO - Meyke Machrita Mamahit (Universitas Negeri Malang, 2025)
Abstract: This study aims to analyze the effect of several leadership styles that are collaborated (collaborative leadership style) on teacher performance, the effect of work motivation (extrinsic and intrinsic) on teacher performance, and the simultaneous effect of several leadership styles that are collaborated (collaborative leadership style) and work motivation (extrinsic and intrinsic) on teacher performance in private senior high schools in Manado City. This research was conducted at 13 private senior high schools in Manado City. The approach used in this study is quantitative, with descriptive survey methods and multiple linear regression analysis. Data were collected using research questionnaires and document analysis. The sample consisted of 64 teachers, taken by proportional random sampling technique from a total population of 211 teachers in private senior high schools in Manado City. The findings of the study show that: (1) there is a positive effect of several leadership styles that are collaborated (situational leadership style) on the performance of private senior high school teachers in Manado City, (2) there is a positive effect of work motivation (extrinsic and intrinsic) on the performance of private senior high school teachers in Manado City, and (3) there is a simultaneous positive effect of several leadership styles that are collaborated (situational leadership style) and work motivation (extrinsic and intrinsic) on the performance of private senior high school teachers in Manado City. The findings of this study recommend that: (1) to improve the performance of private senior high school teachers in Manado City, principals should be able to adapt and make effective several leadership styles that are collaborated (situational leadership style) according to the situation and condition, needs, maturity, and ability of teachers; (2) principals should be able to improve teachers’ work motivation (extrinsic motivation); (3) teachers should increase their intrinsic motivation; and (4) further research should be conducted to explore other variables besides those analyzed in this study. Keywords: Leadership style, work motivation, teacher performance Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh dari beberapa gaya kepemimpinan yang dikolaborasikan (gaya kepemimpinan kolaboratif) terhadap kinerja guru, pengaruh motivasi kerja (ekstrinsik dan intrinsik) terhadap kinerja guru, dan pengaruh beberapa gaya kepemimpinan yang dikolaborasikan (gaya kepemimpinan kolaboratif) dan motivasi kerja (ekstrinsik dan intrinsik) secara simultan terhadap kinerja guru di SMA Swasta Kota Manado. Penelitian ini dilaksanakan pada 13 SMA Swasta di Kota Manado. Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif dengan metode survey deskriptif dan analisis regresi linier berganda. Data dikumpulkan dengan menggunakan kuesioner penelitian, dan analisis dokumen. Jumlah sampel 64 guru, yang diambil dengan teknik proporsional random sampling dari jumlah populasi 211 guru di SMA Swasta Kota Manado. Temuan penelitian menunjukkan bahwa: 1) terdapat pengaruh positif beberapa gaya kepemimpinan yang dikolaborasikan (gaya kepemimpinan situasional) terhadap kinerja guru SMA Swasta di Kota Manado, 2) terdapat pengaruh positif motivasi kerja (ekstrinsik dan intrinsik) terhadap kinerja guru SMA Swasta di Kota Manado, dan 3) terdapat pengaruh positif secara simultan beberapa gaya kepemimpinan yang dikolaborasikan (gaya kepemimpinan situasional) dan motivasi kerja (ekstrinsik dan intrinsik) terhadap kinerja guru SMA Swasta di Kota Manado. Temuan penelitian ini merekomendasikan bahwa:1) untuk meningkatkan kinerja guru SMA swasta di kota manado, kepala sekolah harus mampu mengadaptasikan dan mengefektifkan beberapa gaya kepemimpinan yang dikolaborasikan (gaya kepemimpinan situasional) terhadap situasi dan kondisi, kebutuhan, kematangan, dan kemampuan guru, 2) kepala sekolah harus mampu meningkatkan motivasi kerja guru (motivasi ekstrinsik), (3) guru harus meningkatkan motivasi intrinsiknya, dan (4) penelitian lanjutan hendaknya dilakukan untuk mengeksplorasi variabel lain selain variabel yang telah dianalisis dalam penelitian ini. Kata kunci: Gaya kepemimpinan, motivasi kerja, kinerja guru